Novel Strategies for Sedentary Behavior Research. Issue 6 (June 2015) - Rosenberg, Dori E.; Lee, I-Min; Young, Deborah Rohm; Prohaska, Thomas R.; Owen, Neville; Buchner, David M.
ABSTRACT Purpose This article reports on the "Novel Strategies for Sedentary Behavior Research" session of the Sedentary Behavior: Identifying Research Priorities workshop. Methods The purpose of this session of the workshop were to propose strategies for accomplishing a research agenda in dealing with sedentary behavior and to consider research priorities for people at high risk for excess sedentary behavior. Results and Conclusions The four major recommendations from this workshop were as follows: 1) To add repeated objective measures of physical activity and sedentary behavior to existing cohort studies and standardize approaches to measurement and analysis. Epidemiologic studies will be the most efficient design for addressing some research questions. 2) To increase research efficiency, consider the advantages of a network of connected research studies and health systems. Advantages include access to existing data in electronic health records. 3) To carefully select a variety of high-risk study populations and preplan collaboration among studies in intervention research. This strategy can efficiently address the breadth of issues in sedentary behavior research. 4) To include comparative effectiveness designs and pure environmental interventions in intervention research. This strategy facilitates and enhances translation of interventions into practice.